Análise de máquinas agrícolas distribuidoras de fertilizantes segundo requisitos projetuais - Flores, Eduardo Fiorin (2008)
The Brazilian agriculture develops year by year. Nowadays, it is noticed that studies addressed for a constant increase for an implantations of technological systems in machineries and management of rural properties are accomplished, offering this way options in that the technology applied in a property can provide better results in production, in quantity, in quality, in cost for agricultures implantations, and in structuring of the soil focusing the environment. The applied technology can allow a variation of the dosage in elapsing of cultivation applying the dose already recommended for each bars lifted up, measured and implanted in the system. The objective of this work was to accomplish a survey of information and an analysis on distributors of fertilizers machines disposed in the Rio Grande do Sul State market, verifying if manufacturers of those machines uses some type of reference model for development of the product, looking for in that way to evaluate the level of satisfaction of the projetuais requirements, because, it is known that the deficiency in application of models for to project machines is enormous in Brazil, basing a lot on the " attempt " and " error", therefore, the demand of studies for the development of products is larger, in the search of the customer's satisfaction. The data were collected through the application of questionnaires to identify the occurrence of the accomplishment of the ten most important design requirements, already hierarchized by the tool QFD for its degree of importance, besides deepen the accomplish of pamphlets that characterize the models of distributors of fertilizers, as well as sites exploration linked to this type of machinery. The collection of information was accomplished and addressed the satisfaction of the requirements and users. The questionnaires were applied to technicians responsible for the analyzed models and to the own users, gathering information of each fertilizer dosager machine studied in the research, verifying if it accomplishes or not the requirements determined by Menegatti (2004). It is noticed, through this work that 18 (eighteen) models of distributors do not accomplish 50% of the project requirements, and that most of the models, 44 (forty-four) models of 69 (sixty-nine) analyzed accomplish 50% of the requirements exactly, and the maximum number of accomplished requirements was 7 (seven), where two models just satisfied those requirements. No model accomplished all the requirements, even so everyone accomplished some type of a projetual requirement, introducing none below 4 (four). With that, you can use this survey to identify the lack of each machine, allowing as soon as possible develop new actions in the projection of the machine so that it has the requirement of analyzed project and present satisfactorily.